Convection initiation - Zahra Ghassabi; Hoshang Ghaemi; Ebrahim Mirzaei (تحقیقات کاربردی علوم جغرافیایی)
The structure of deep moist convection can be influenced by various factors, including wind shear, available potential energy of convection, relative humidity, and vertical distribution of these variables. Among these factors, wind shear plays a more significant role in the creation of convection. The interaction between large-scale and synoptic-scale processes, along with the adjustment of available potential energy for convection and the presence of convection inhibitors, creates conditions suitable for the development of convection. The large-scale average reduces the convection inhibitor, while even small vertical velocities, such as a few centimeters per second, can have a noticeable impact on the environment's sounding. The presence of potential instability is also considered an important factor in initiating deep moist convection. When the temperature reaches the critical point and the convection inhibitor is removed, moist deep convection begins. If an air parcel rises above the lower stable layer with low relative convective inhibition energy and high relative free convective potential energy, it supports the development of deep moist convection. The initiation of updrafts by warm air masses and the subsequent development of convection depend on parameters like vertical wind shear and the inversion cap of the environment, among others. Large-scale convective systems can be triggered with less forcing due to the significant uplift of the air mass from the surface to the convection level along the front.